Chinatown Children during World War Two in The Jade Peony - Liu, Zhen (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2018)
In The Jade Peony (1995) Wayson Choy captured vividly the lives of three children growing up in Vancouver’s Chinatown during the 1930s and 1940s when the Depression and the Second World War constituted the social backdrop. In the article, I argue that the Chinatown residents exemplify the type of vulnerability defined by Judith Butler as "up-againstness" and especailly the children in the novel suffer from a greater vulnerability as they are caught up in the crossfire of both sides. Growing up in two conflicting cultures and restricted to the liminal cultural and physical space, the children are disorientated and confused as if stranded in no man’s land. More importantly, in their serious struggles, the children show great resilience and devise their own strategies, such as forming alliance with others, to survive and gain more space in spite of the many restraints imposed on them.